Fostering Learner Autonomy: Evaluating the Effectiveness of the Problem-Based Learning Approach - Sari, Sindi Kartika; Bahri, Saiful; Wahyudi, Waluyo Erry (Papanda Publisher, 2025)
This study investigates the effectiveness of the Problem-Based Learning (PBL) model in fostering learning autonomy among Grade X students in Islamic Religious Education at SMAN 15 Bandar Lampung. The research was motivated by the critical need to develop students' independent learning capabilities within educational contexts. A quantitative approach employing a quasi-experimental design with posttest-only control group framework was utilized. Participants were selected through simple random sampling, resulting in Class X.E 3 (n=31) as the experimental group receiving PBL instruction and Class X.E 1 (n=30) as the control group taught through direct instruction. Data collection employed a validated questionnaire measuring five dimensions of learning autonomy: learning motivation, self-regulation, independent decision-making, ability to overcome difficulties, and self-reflection capacity. The instrument comprised 12 validated items from an original 20-item questionnaire, demonstrating reliability coefficient of 0.603. Statistical analysis included normality testing using Liliefors test, homogeneity assessment through Bartlett's test, and hypothesis testing via independent samples t-test. Results revealed statistically significant differences between groups with t-value of 6.637 and significance level of 0.000 (p < 0.001). The experimental group achieved substantially higher learning autonomy scores with a mean difference of 8.318 points. These findings indicate that PBL implementation significantly enhances students' learning autonomy compared to traditional direct instruction methods. The study concludes that PBL serves as an effective pedagogical strategy for developing independent, engaged, and self-directed learning behaviors, recommending its broader adoption in Islamic Religious Education contexts.